g-3/7=27

Simple and best practice solution for g-3/7=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g-3/7=27 equation:



g-3/7=27
We move all terms to the left:
g-3/7-(27)=0
determiningTheFunctionDomain g-27-3/7=0
We multiply all the terms by the denominator
g*7-3-27*7=0
We add all the numbers together, and all the variables
g*7-192=0
Wy multiply elements
7g-192=0
We move all terms containing g to the left, all other terms to the right
7g=192
g=192/7
g=27+3/7

See similar equations:

| 2/5x–3/7=1–4/7x | | {8+h}{10}=1​ | | 2x+3x-(x+4)=11 | | 9c–6=2c+15 | | {8+h}{10}=1 | | (x-44)+48=180 | | x-9=-x+21 | | -3x+10=-6x-4 | | -12=-2a=6 | | 3(x-5)=20+x+5 | | 2k=3k+6 | | 3+4(7-2x)=-1-(x+5) | | b^-4=1/3 | | 5x-7+4+3x=29 | | 3n=25–2n | | (3x+10)+(x+40)=(6x) | | -12=12a+6 | | 13x+23=12x+19 | | 3+4x(7-2x)=-1-(x+5) | | 7(n+4)=45 | | 1x+8=5x-5-3x | | 11/2n-2=8 | | x+8=5x-5-3x | | -73=4m=3 | | (x-44)+49=180 | | –4p–16=4p | | 9(x+7)=5(x+5) | | 7x-20=4x+13 | | 3x-4=4-(-5x+6) | | y4-10=-14 | | 21/4m+6=7 | | .5(2p–3)–3(3p–7)=5 |

Equations solver categories